A hybrid inverter solution for medium voltage applications using series capacitor and a CSI Active Power Filter (SC-APF) - Papadopoulos, Savvas; Rashed, Mohamed; Klumpner, Christian; Wheeler, Patrick (2014)
This paper proposes a new hybrid inverter solution for medium/high voltage applications that consists of a slow switching inverter using high voltage or series connected switching devices, fitted with a low kVA rated auxiliary current source inverter to cancel the switching ripple produced by the main inverter. The reduction in CSI voltage stress is obtained by connecting it to the MV grid via a series capacitor which makes the solution suitable for retrofitting older inverters equipped with large passive filters. The paper describes the design procedure, the control scheme and validates the feasibility of the idea by including simulation results and evaluation of the waveform quality and also an estimation of the semiconductor losses.